Les risques catastrophiques et l’assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1989)
The first part of this article gives the general classification which distinguishes natural, accidental and criminal catastrophes and, finally, the major risks involving the various types of liabilities. The second part of this article presents the catastrophic risks which have occurred since the beginning of the 1970's and examines the different insurance coverages available.